OPTIMIZATION AND CHARACTERIZATION OF ION ACTIVATED OCULAR IN-SITU GEL FORMULATION FOR BACTERIAL CONJUNCTIVITIS - KAPOOR, ANKITA; GUPTA, G. D. (International Journal of Applied Pharmaceutics, 2020)
Objective: The present research work aims at describing the formulation, optimization and evaluation of ion activated ocular in-situ gel of gatifloxacin for treatment of bacterial conjunctivitis so as to overcome patient inconvenience, precorneal drug elimination, variation in efficacy, vision blurring and frequent instillation associated with conventional eye drops and ointments. Methods: In-situ gel was prepared using gellan gum as an ion activated phase transition polymer and HPMC K100M as release retardant. Gatifloxacin was characterized by spectrophotometry. Crystalline state of the drug was determined using X Ray Diffraction study. The developed formulation exhibited instantaneous gel formation in simulated lacrimal fluid (pH 7.4), which was further evaluated for its rheology, irritancy parameters, in vitro release, trans-corneal permeation and antimicrobial activity. Results: Gatifloxacin exhibited λmax 286 nm obeying Beer Lambert’s law and pH-dependent solubility at a pH range of 2 to 4. 0.6% gellan gum and 0.4% HPMC K100M were optimized in the formulation which exhibited a viscosity of 55 cps in sol form and 325 cps in gel form with pseudoplastic behavior and prolonged in vitro release. Permeation of formulation was 75.8% in 7 h with log P of drug 0.59. Developed isotonic and non-irritant formulation had a lower apparent permeability coefficient of 8.15 x 10-5 cm/sec as compared to marketed formulation. Conclusion: A Formulation can be viewed as an efficacious medicine by virtue of its higher zone of inhibition, ability to enhance precorneal residence time and consequently ocular bioavailability with lesser frequency of administration attributed to slow and prolonged diffusion of the drug from the polymeric solutions.